Factors Affecting Impulse Purchasing of Filipino Consumers in Convenience Stores - Borromeo, Ellaine A.; Cai, Ginger Alexandra C.; Etrata, Antonio E. (IJOSMAS, 2022)
This study examined Filipino consumers' intrinsic and extrinsic factors in convenience stores, including impulse buying tendency, availability of money, time availability, visual merchandising, in-store environment, and sales promotions. A significant sign of consumers' purchasing decisions was triggered by impulse buying. Studies of this behavior have been a great advantage for business owners who want to generate more enormous profits. However, only limited studies about impulse buying behavior have been conducted here in the Philippines. The study followed a mixed-method approach since it was under the explanatory side of the said method. It aimed to understand the factors affecting the impulsivity of Filipino consumers when they are inside a convenience store. The study was limited to external variables like the number of respondents. However, the researchers provided a factor analysis on intrinsic and extrinsic variables that will enhance the research. The independent variables have been used to find out the correlation between these variables, such as impulse buying tendency, money availability, time availability, visual merchandising, in-store merchandising, and sales promotion. The study's primary limitation is that the survey does not include different age groups. Further tests with illustrations from different age groups may lead to more precise outcomes. The impulsiveness of these individuals in risky conclusions might affect impulse buying behavior. Hence, the research shall test various age groups to determine the influence of such a factor. Keywords: convenience store, impulse buying, in-store environment, sales promotions